Stop playing safe rethink risk, unlock the power of courage, achieve outstanding success - Warrell, Margie (Gildan Audio, 2020)
Stop Playing Safe speaks to the heart of what holds people back in their professional lives, making the sharp distinction between knowing what to do, and having the courage to do it. In explaining why playing safe can be a high-risk strategy, it provides a framework to meet the challenges of the pressure-laden workplace that can so easily siphon passion from employees, disconnecting them from themselves and from the intrinsic value of what they do each day. It includes the insights and experiences of high profile leaders and entrepreneurs who have achieved outstanding success in their professional lives, and what they did (and didn't do) that made the difference as they forged their own path forward.Broken into two sections, the first section "Core Courage" is focused on building the foundation for courageous action. The second section "Courage in Action" is broken into five core courage challenges: Challenge, Speak, Adapt, Leverage, and Lead. Each chapter contains proven "how to" strategies the reader can apply to better assess risk, leverage their strengths, manage conflict, be decisive amidst uncertainty, be a catalyst for change in their organization, and expand their network of influence.